PENINGKATAN KEMAMPUAN MENULIS AKSARA JAWA KELAS III MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE: IMPROVING THE ABILITY TO WRITE JAVANESE SCRIPT IN GRADE III THROUGH SCRAMBLE TYPE COOPERATIVE LEARNING MODEL - Rahma, Ramadhani Oktavia; Setyawan, Agung (CV. Kalimasada Group, 2023)
The motivation behind this study stems from the fact that most elementary school students find learning Javanese script material challenging because they have difficulty remembering many forms of characters. This study aims to improve the writing skills of third grade students of SDN II Pengumbulanadi Javanese script by using a cooperative learning model scramble type. This study uses classroom action research approach to investigate how to improve students ' ability to write Javanese script. Ten third grade students of Sdn II Pengumbulanadi became the subject of research. Field notes, observations, testing, interviews, and documentation are some of the tools used in this study. The results showed that the use of scramble-type cooperative learning model significantly improved the results. The average score during the pre-cycle phase was 53. Only five students met the graduation requirements in the first cycle, when the average score rose to 61. The class average increases to 78 in the second cycle, and each student meets the graduation requirements. Based on these findings, it can be said that students ' proficiency in writing Javanese script increased when scramble-type learning paradigm was used.